The effect of continuous and pulse feeding Lactiplantibacillus plantarum on growth performance, gut microbiota, immunological, haematological and plasma biochemical parameters of rainbow trout Oncorhynchus mykiss - Ivana Mikulíková; Marija Radojičić; Hana Banďouchová; Jana Blahová; Ondřej Malý; Ivana Papežíková; Hana Novotná; Eva Poštulková; Zuzana Lepková; Ivona Toulová; Klára Odehnalová; Jan Mareš; et al. (Italian Journal of Animal Science)
A potentially probiotic autochthonous strain of Gram-positive lactic acid bacteria, Lactiplantibacillus plantarum R2 Biocenol™ (CCM 8674), was assessed as a feed supplement in rainbow trout Oncorhynchus mykiss. Three treatment groups were compared; control, fish provided L. plantarum as a four-week dietary pulse followed by three weeks of non-supplemented diet and fish provided the supplemented feed for seven weeks. A trend of improved growth performance (specific growth rate, feed conversion ratio) was observed in both supplemented groups. Though the effect of pulse supplementation on the intestinal microbiome community was not permanent, a statistically significant difference was recorded in the composition of the gut content bacterial community in both pulse and continuous supplemented groups. A significant reduction in the abundance of several bacterial genera was observed in the gut microbiome of fish given the seven-week supplementation. Continuous supplementation significantly increased blood haemoglobin and haematocrit levels and reduced plasmatic chloride concentration, while significantly increased concentrations of plasmatic magnesium and calcium were recorded in pulse-fed fish. No significant changes in immunological indices were revealed. Our results suggest that four weeks and seven weeks supplementation of L. plantarum show similar trends of effects on growth performance in rainbow trout. Further studies will follow to assess the effects of L. plantarum R2 Biocenol™ on the response of rainbow trout to a pathogens challenge in relation to the change in gut microbiome composition.